Postmastectomy Breast Reconstruction in Patients with Non-Metastatic Breast Cancer: A Systematic Review. - Zhong, Toni; Fletcher, Glenn G.; Brackstone, Muriel; Frank, Simon G.; Hanrahan, Renee; Miragias, Vivian; Stevens, Christiaan; Vesprini, Danny; Vito, Alyssa; Wright, Frances C. (Current Oncology, 2025)
Breast reconstruction after mastectomy improves the quality of life for many patients with breast cancer. There is uncertainty regarding eligibility criteria for reconstruction, timing (immediate or delayed—with or without radiotherapy), outcomes of nipple-sparing compared to skin-sparing mastectomy, selection criteria and surgical factors influencing outcomes of nipple-sparing mastectomy, prepectoral versus subpectoral implants, use of acellular dermal matrix, and use of autologous fat grafting. We conducted a systematic review of these topics to be used as the evidence base for an updated clinical practice guideline on breast reconstruction for Ontario Health (Cancer Care Ontario). The protocol was registered on PROSPERO, CRD42023409083. Medline, Embase, and Cochrane databases were searched until August 2024, and 229 primary studies met the inclusion criteria. Most studies were retrospective non-randomized comparative studies; 5 randomized controlled trials were included. Results suggest nipple-sparing mastectomy is oncologically safe, provided there is no clinical, radiological, or pathological indication of nipple-areolar complex involvement. Surgical factors, including incision location, may affect rates of complications such as necrosis. Both immediate and delayed reconstruction have similar long-term outcomes; however, immediate reconstruction may result in better short to medium-term quality of life. Evidence on whether radiotherapy should modify the timing of initial reconstruction or expander-implant exchange was very limited; studies delayed reconstruction after radiotherapy by at least 3 months and, more commonly, at least 6 months to avoid the period of acute radiation injury. Radiation after immediate reconstruction is a reasonable option. Surgical complications are similar between prepectoral and dual-plane or subpectoral reconstruction; prepectoral placement may give a better quality of life due to lower rates of long-term complications such as pain and animation deformity. Autologous fat grafting was found to be oncologically safe; its use may improve quality of life and aesthetic results.